Some remarks on laghu-tattva-sphota XXI.9-24 - Glinicka, Małgorzata (Hybris, 2015)
The article is aimed at analysis of 9–24 stanzas of XXI chapter of philosophical poem Laghu-tattva-sphoṭa, i.e. A Light Bursting of the Reality, authored by Amṛtachandra-sūri (10th c. A.D.), the Jain thinker. Chapter XXI is dedicated to the problem of universals and particulars, meaningful and influential subject of Indian, as well as Western philosophy.